Extracranial vertebral artery to middle cerebral artery bypass in therapeutic internal carotid artery occlusion for epipharyngeal carcinoma: A technical case report - Ota, Nakao (Surg Neurol Int, 2021)
BACKGROUND: Vertebral artery (VA) to middle cerebral artery (MCA) bypass is a rarely selected technique because a complex expanded dissection is required, and often, a better donor artery than VA exists. A good indication for VA-MCA bypass is the treatment of head-and-neck malignancies with the sacrifice of the internal carotid artery (ICA) or for carotid artery rupture. METHODS: A 23-year-old man with epipharyngeal carcinoma, treated by ligating the carotid artery with a VAMCA bypass before chemoradiotherapy, was reported. Radiographic findings showed that the bone of the carotid canal was dissolved, and the right ICA was engulfed by the tumor. As epipharyngeal carcinoma is hypersensitive to radiation, in cases where the tumor rapidly disappears, ICA may dangle in the pharynx and rupture may occur. In addition, to irradiate sufficiently, the ICA may become an obstacle. Hence, we decided to perform carotid ligation with a VA-MCA bypass before radiation and chemotherapy for the primary lesion. We selected the V3 portion of the VA as the donor on the ipsilateral side, as it can supply high-flow cerebral blood flow, which is not influenced by carcinoma and less influenced by irradiation for the epipharynx. RESULTS: The VA-MCA bypass was completed without complications followed by endovascular occlusion of the ICA. Induction chemotherapy was initiated for the patient 2 weeks after surgery. The patient achieved a complete response following chemoradiotherapy. CONCLUSION: ICA ligation with VA-MCA high-flow bypass earlier than chemoradiotherapy is useful for epipharyngeal carcinoma as it prevents carotid artery rupture and allows radical intervention.